IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KECAMATAN KANIGARAN KOTA PROBOLINGGO - Eko Yudianto Yunus (REFORMASI, 2019)
Crucial food aid Examples of Non Cash (BPNT) Program is a program of food subsidies as a form of government efforts to increase food security and provide protection to poor families through the distribution of rice. Each family will receive Rp. 110.000,- /month the point of distribution. Researchers take focus in Kecamatan Kanigaran Kota Probolinggo. In fact, implementation of BPNT policy is not always consider full-on procedure policy as depending on condition and situation in society. The objective of this study is to analyze the implementation of the Crucial food aid Examples of Non Cash program. This research uses qualitative descriptive method. Data collection was carried out with in-depth interviews from various informants have been determined. In qualitative research, data retrieved from various sources by using a technique of collecting data of which various (triangulation) and continuously until it is saturated. The result of this research is the determining factors of BPNT program implementation in, Kecamatan Kanigaran Kota Probolinggo caused by attitude factors (disposition) which is less successful in rice quality, target the household beneficiaries Crucial food aid Examples of Non Cash (BPNT), the number of households that received rice target beneficiaries.